2008
DOI: 10.1097/mlg.0b013e31816422ea
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Multilevel Surgery of the Upper Airway in Adults With Obstructive Sleep Apnea/Hypopnea Syndrome

Abstract: Multilevel surgery for OSAHS is obviously associated with improved outcomes, although this benefit is supported largely by level 4 evidence. Future research should focus on prospective and controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
243
1
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 257 publications
(263 citation statements)
references
References 61 publications
7
243
1
12
Order By: Relevance
“…17 On statistical analysis, two patients in our study underwent tonsillectomy with uvuloplasty as a sole surgical treatment for OSA. And these two patients improved well without any complications accounting a success rate of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…17 On statistical analysis, two patients in our study underwent tonsillectomy with uvuloplasty as a sole surgical treatment for OSA. And these two patients improved well without any complications accounting a success rate of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a combination of procedures to address airway obstruction at multiple levels may improve success compared to single-site therapy [7,8,51,52]. For example, a nasal procedure may be performed in combination with an oropharyngeal procedure.…”
Section: Multi-level Surgery and Staged Surgerymentioning
confidence: 99%
“…Data suggests that only 25 % of patients present with a uni-level obstruction, whereas 75 % had multi-level obstruction sites [52]. Evidence has shown that single-site surgery has a poor success rate when multilevel obstruction is present.…”
Section: Sleep Apnea Surgery In Childrenmentioning
confidence: 99%
“…They identified 12 randomized controlled trials studying palatal implants, radiofrequency surgery, maxillomandibular advancement and uvulopalatoplasty and concluded that high quality trials studying surgical treatment are feasible and can lead to recommendations with high levels of evidence [14]. Other authors concluded in a systematic review that, in a certain percentage of OSA patients who either fail or are unwilling to pursue CPAP therapy, multilevel OSA surgery offers a chance to control their OSA [15].…”
Section: Introductionmentioning
confidence: 99%